已知\( y = \sin x + \cos x \),则 \( dy = (\cos x - \sin x)dx \)( ).
举一反三
- 已知\( y = \cos x \),则\( dy \)为( ). A: \( \cos x \) B: \( {\rm{ - }}\sin x \) C: \( \cos xdx \) D: \( {\rm{ - }}\sin xdx \)
- 已知\( y = \cos x \),则\( y' \)为( ). A: \( \cos x \) B: \( \sin x \) C: \( - \cos x \) D: \( - \sin x \)
- 已知\( {y^{(n)}} = \cos x \),则\( {y^{(n + 2)}} \)为( ). A: \( \sin x \) B: \( - \sin x \) C: \( \cos x \) D: \( - \cos x \)
- \( \int { { {\cos 2x} \over {\sin x - \cos x}}dx} = \)( ) A: \(\sin x + \cos x + C \) B: \( - \sin x + \cos x + C \) C: \( - \sin x- \cos x + C \) D: \( \sin x - \cos x + C \)
- 【单选题】设y=sin(cos(x)),求 结果为:(本题10.0分) A. cos(cos(x))*cos(x)+ sin(cos(x))*sin(x)^2 B. - cos(cos(x))*cos(x) - sin(cos(x))*sin(x)^2 C. - cos(cos(x))*cos(x)^2 - sin(cos(x))*sin(x)^2 D. - cos(cos(x))*cos(x) ^2- sin(cos(x))*sin(x)